(untitled) (Eurasian Medical Research Periodical, 2022)
The article presents data on the physiological parameters of the crosses of chickens DeKalb White and Loman LSL. Parameters of live weight, egg weight, body temperature and respiratory rate. The difference in these parameters among crosses is shown starting from the age of four months for 6 months